33. EFFECTIVENESS OF SELF-DIRECTED LEARNING ACTIVITIES FOR MEDICAL STUDENT IN CLINICAL SIMULATION ENVIRONMENT (Vietnam Journal of Community Medicine, 2025)
Objective: To assess the improvement in the competencies of medical students after participating in Self-Directed Learning (SDL) activities.Method: A descriptive cross-sectional study was conducted on 224 second-year medical students who participated in SDL activities.Results: The average results of the group participating in the sessions were significantly higher in 6 out of 9 skill stations compared to the group of students who did not participate in the sessions.Conclusion: The initial results of SDL activities demonstrate effectiveness in outcome competencies in some skills. Scaling up the SDL model for other student cohorts to improve competency in required skills should be implemented and evaluated in future studies.
Keywords: Self-directed learning; clinical simulation; basic medical skills; basic clinical skills